PENYAKIT HIPERTENSI PADA LANSIA DI DESA HURABA KECAMATAN BATANG ANGKOLA KABUPATEN TAPANULI SELATAN TAHUN 2020: Hypertension, Elderly, Lifestyle - Nasution, Lisna Khairani; Rambe, Norma Yanti (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2020)
Hypertension can be defined as persistent blood pressure where the systolic pressure is above 140 mmHg and the diastolic pressure is above 90 mmHg. Hypertension is said to be mild if the diastolic pressure is between 95-104 mmHg, moderate hypertension if the diastolic pressure is between 105 and 114 mmHg and severe hypertension when the diastolic pressure is 115 mmHg or more. This division is based on an increase in diastolic pressure because it is considered more serious than an increase in systolic (Padila, 2013). The wrong diet is one of the risk factors that increase hypertension. Junk food is a major contributor to hypertension. Excess fat intake causes fat levels in the body to increase, especially cholesterol which causes weight gain so that blood volume experiences a greater increase in pressure. Excess sodium intake will increase extracellular causing blood volume which has an impact on the onset of hypertension. Lack of consuming food sources containing potassium causes the amount of sodium to accumulate and will increase the risk of hypertension (Junaedi, et al. 2013).Benteng Huraba Village is one of the villages in Batang Angkola sub-district, South Tapanuli district which has a fairly large number of elderly, the purpose of community service is to provide information to the community, especially the elderly regarding knowledge about hypertension disease counseling in the elderly in Huraba village, Batang Angkola district South Tapanuli with 42 elderly people. The results of this community service were enthusiastically received by the elderly in Benteng Huraba Village as seen from the many elderly who asked about information about the dangers of hypertension and its causes, where the habit of drinking coffee increases the risk of hypertension, but it depends on the frequency of daily consumption. Drinking coffee and smoking can stimulate constriction of blood vessels so that it can increase blood pressure.Knowledge about the importance of knowing the dangers of hypertension is very useful for the community, especially the elderly in Huraba Village, Batang Angkola District, with this knowledge, it is hoped that it will change the wrong lifestyle, change unhealthy habits and family members are expected to be able to maintain diet so that the elderly live healthier.